THE EFFECT OF INFLATION, BI 7 DAY (REVERSE) REPO RATE AND RUPIAH EXCHANGE RATE ON THIRD PARTY FUNDS OF ISLAMIC COMMERCIAL BANKS IN INDONESIA - Arista Ramadanika; Mutia Pamikatsih; Suwono Suwono; Ishfaq Ahmed (Universitas Islam Darul 'ulum Lamongan, 2025)
As a financial institution, the main problem generally faced by Islamic banks is funds. Banks are unable to operate and function properly if there are inadequate funds. Third-party funds from the public play an important role in the sustainability of a bank. On the other hand, macroeconomic aspects can affect the collection of third party funds for banks. This study was conducted with the aim of knowing the effect of inflation, rupiah exchange rate, and BI 7 Day (Reverse) Repo Rate on Third Party Funds of Islamic Commercial Banks in Indonesia. In this study, the data analyzed consisted of quarterly data covering the period from the first quarter of 2020 to the fourth quarter of 2023. The sampling method used purposive sampling and 7 Islamic commercial banks were used as samples. Data analysis uses the Panel Data Regression Analysis method operated through the Eviews program. The results showed that inflation and the BI 7 Day (Reverse) Repo Rate had an effect on third party funds while the rupiah exchange rate had no effect on third party funds of Islamic commercial banks in Indonesia.